The development of Indonesian social policy in the context of overseas development aid - Brooke Wilmsen; Alexandra Kaasch; Mulyadi Sumarto (United Nations Research Institute for Social Development (UNRISD), 2017)
In the last decade, social protection has risen in prominence as a strategy to address poverty and vulnerability in developing countries (Barrientos 2011). International organizations such as the United Nations and development banks have adopted strategies and policies on social protection.1 To this end, the International Labour Organization's (ILO) role in promoting social protection floors has been particularly prominent (Deacon 2013). Less is known about the role that Overseas Development Assistance (ODA) plays in the reform of social protection. ODA typically supports the social sector in recipient countries in various ways: general budget support, funding for particular projects with social objectives or investment in infrastructure, such as schools or hospitals. However, it is in filling the gaps in the social programmes of emerging economies that ODA can be most effective. [...] By observing the PRSF we observe the actioning of many of the principles of aid effectiveness as outlined in the Paris Declaration. In its engagement with the Government of Indonesia (GoI), Australia acted as a "constructive partner" rather than a "demanding donor", which contributed to the recipient government retaining ownership over its activities. Two other principles of aid effectiveness - harmonization and alignment - were also observed. The PRSF was embedded within the Indonesian governance structures and operated in a manner that was sensitive to the political culture of the Indonesian bureaucracy. Finally, this paper suggests that two-way transformation can occur as a result of effective ODA investment in social protection reform.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330